Scale Development of Aofa Farm Limousin Cattle Business Based on Investment Feasibility Analysis - Hadyan Lucky Al Faroby; Rosiana, Nia (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Beef supply in Indonesia has not been able to reach demand. Currently, the need for livestock is increasing, so it is necessary to develop cattle farming. Aofa farm is a cattle farm that focuses on fattening limousine cattle that sells its products only during Eid al-Adha. Aofa farm plans to its business by increasing the number of cattle pens, increasing the number of limousine cattle, and purchasing concentrate feed. In addition, there was an increase in the price of limousine cattle seeds, an increase in feed prices, and a decrease in sales of limousine cattle. So necessary for it to analyze the feasibility of Aofa Farm's limousine cattle farm based on non-financial aspects financial aspects, and switching value analysis. The results of the feasibility of the non-financial aspects of the development of Aofa Farm are feasible to run based on descriptive analysis and quantitative analysis which shows the feasibility score on each non-financial aspect of more than 50 percent. The results of the financial aspect analysis obtained an NPV value of Rp 2,674,602,815, Net B/C of 8.39, IRR of 88.15 percent, and Payback Period of 2.26 years which shows that the Aofa Farm development plan is feasible to run based on financial aspects because the value obtained exceeds the eligibility criteria. The results of the switching value analysis show that Aofa Farm is sensitive to a decrease in limousine cattle sales.